Moderasi Ukuran Pemerintah Daerah pada Pengaruh Kinerja Keuangan Daerah dan Transparansi Daerah Terhadap Tingkat Korupsi - Muhammad Azizi Yusuf; Diah Hari Suryaningrum (Universitas Muhammadiyah Metro, 2022)
This study aims to examine and analyze the effect of regional financial independence, local investment, and transparency on the level of corruption moderated by the local government size. The study population is 34 Provincial governments in Indonesia from 2016 to 2020. The sample is selected using census techniques. The data analysis technique is multiple linear regression analysis and moderated regression analysis using Statistical Product and Service Solution 25 software. The results state that regional financial independence affects the corruption level, whilst local investment and transparency don't affect the level of corruption. Then the local government size moderates the effect of regional financial independence on the level of corruption. Otherwise, local government size doesn't moderate local investment and transparency on affected the level of corruption.